Pengembangan Program Media Handbook Persiapan Masa Pubertas Bagi Anak Penyandang Disabilitas Intelektual - Haliqa, Salsabila; Homdijah, Oom Sitti; Ahklan, Riksma Nurahmi Rinalti (Universitas Negeri Padang, 2024)
Puberty is an important period in children's development, including mentally retarded children. This process involves significant physical, emotional, and social changes. For children with intellectual disabilities, preparation for puberty requires a very structured and focused approach to understand and handle these changes well. Every teenager will generally experience puberty. Puberty in teenagers with special needs is actually the same as teenagers in general, namely it is marked by physical, hormonal and psychological changes. Adolescents with special needs who have started to enter pre-puberty need to receive guidance on pre-menstrual skills as soon as possible. However, for teenagers with special needs who experience intelligence barriers, it will be difficult if it is not taught from the start because Tuangrahita students have difficulty understanding abstract information about the concept of puberty and the steps for using and cleaning sanitary napkins. One of the appropriate media in providing pre-menstrual skills education is very necessary. Handbook media is a book that contains pictures, information, instructions, etc. which serve as guidance for readers to know something in full, such as the steps for installing sanitary napkins and cleaning sanitary napkins in preparation for puberty for children with intelligence barriers when children are already menstruating. Use of methods Demonstration with material on using and cleaning a napkin makes students understand and understand the steps for using and cleaning a napkin properly and correctly, because in this lesson the teacher demonstrates one by one the steps for using and cleaning a napkin and the students immediately practice it directly. The aim of this research is to determine the increase in understanding of the concept of puberty and skills in using and cleaning sanitary napkins by direct learning using the demonstration method for SMALB students with disabilities. This research uses a qualitative approach with a case study design to learn the concept of puberty and to learn skills in using and cleaning sanitary napkins. The research subject was a 17 year old mentally retarded SMALB student with the initials KA. The data collection method in this research is observation, test interviews and documentation. The instruments used to collect data include learning process observation instruments, knowledge test questions and performance test assessment formats. The completeness of classical learning regarding understanding preparation for puberty can be seen from the test results. The results of the student knowledge test at meeting I showed that 61% of students got knowledge test scores at meeting II. The results of the student performance test showed that 69% of students got a test score at the third meeting, the children got a score of 76% and at the fourth meeting they got a score of 85%, and at the fifth meeting, namely the last meeting, the children got a score of 88% in the activity of installing and cleaning sanitary napkins using media. handbook and demonstration method in preparation for puberty. The results of the study concluded that understanding of preparation for puberty and skills in using and cleaning sanitary napkins for mentally retarded SMALB students increased with direct learning using demonstration methods and handbook media.